The concentration of power in the market for contemporary art: an empirical analysis of ArtReview's “Power 100” - Aloys Leo Prinz (SN Business & Economics, 2022)
Art experts and intermediaries play a crucial role in art markets. Artworks are goods whose quality is difficult to determine. Therefore, it seems necessary to restrict competition in the market for art experts to a certain extent, but not too much, in order to provide high-quality know-how. This paper contains an empirical analysis of the extent to which the market for art experts is concentrated. To this end, different methods for measuring the market concentration are applied, with an emphasis on the determination of the distribution function of a newly defined Power Index. The annual Power 100 ranking in the magazine ArtReview from 2002 to 2019 is used to study concentration in the art expert market. The results reveal not only several indications of a hierarchically tiered, but also highly concentrated market power in this market. First, the selection of nationalities of the so-called power members is biased, given that particularly Americans and western Europeans are overrepresented in relation to their world population shares, in contrast to underrepresented Asians, Africans, and Latin Americans. Second, although there is considerable variability in the low tiers of the ranking, the top positions in the rankings are very stable, as shown by the Power Dominance Index. Third, the main empirical result of this paper is that the Top 99 ranking positions follow an extreme value Fréchet distribution with a fat tail. This is interpreted as an indication of excessive concentration on the highest tier of art experts. Liberalizing the art expert market to a certain extent may provide more diversity and less dominance in high-end art markets.
Keywords: C13; C46; L15; L82; Z11; 330; ArtReview; Art intermediaries; Art expert rankings; Concentration of power; Extreme-value distributions